The increasing doses of methotrexate pharmacokinetics after intravenous administration in rats – model selection - Rajšić, Ivana; Pavlović, Nebojša; Milijašević, Boris; Vukmirović, Saša; Spasić, Dragan; Žigić, Miodrag; Grahovac, Nenad; Goločorbin-Kon, Svetlana; Mikov, Momir (Vojnosanitetski pregled, 2021)
Background/Aim. Methotrexate (MTX) plays a significant role in the treatment of various diseases, but the toxicity remains the main issue of its use, especially when administered in high doses. Considering altered pharmacokinetics of MTX as a factor strongly implicated in the large interpatient variability and unexpected toxicity in certain patients, the accurate description of MTX pharmacokinetic behaviour of both low and high doses is of the utmost importance. Therefore, the objective of this study was to determine the pharmacokinetics of MTX after intravenous (iv) administration in ascending doses of 5, 40, 80 and 160 mg/kg in rats and to select the appropriate mathematical model describing MTX pharmacokinetics. Methods. Plasma concentrations of MTX were measured using the liquid chromatography - mass spectrometry (LC/MS) method. Pharmacokinetic parameters were calculated by non-compartmental and two-compartmental integer-order analyses. Results. MTX showed linear pharmacokinetics following iv administration up to the dose of 80 mg/kg. The administration of a high dose of MTX (160 mg/kg) resulted in the similar pharmacokinetic behaviour as when applied in the twice lower dose (80 mg/kg), which can be explained by dose-dependent changes in the expression of solute carrier (SLC) and ATP binding cassette (ABC) transport proteins and intracellular metabolism. Furthermore, the classical two-compartment model could not explain the pharmacokinetics of MTX in a small percentage of experimental animals, which opens up new strategies for the use of fractional order pharmacokinetic models in MTX therapy optimisation. Conclusion. These results of pharmacokinetic analyses may be helpful in adjusting the dosage regimen of MTX, but the application of novel pharmacokinetic models, such as those based on fractional calculus, is still needed in the process of MTX therapy optimisation.